Pembentukan Gelas Keramik Litium Alumino Silikat Dari Zeolit Alam - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Mesin Fak. Teknik UGM, 2003)
Natural zeolite is widely used in adsorption processes. Stabilization of waste zeolit, used particulary in hazardous waste adsorptions, is very important Because of natural zeolite contains glass former oxides, the stabilization is carried out by cry stallization preceded by glass formation. Vitrification temperature of natural zeolit was decreased by addition of a certain amount of soft cullet. The 30% weight addition of shoft cullet could decrease vitrification temperature to 1200Â°C. A certain amount of lithium oxide was mixed with a mixture of zeolite-cullet stoichiometrically to Al203 contained in the mixture based on /3-spodumene composition. Crystallization was conducted in temperature ranging from 675Â°C to 750'C with constant heating rate of 3"C/min. The formed crystal phase was examined by X-ray diffraction analyzer. TiO2 was added to promote heterogeneous nucleation in the glass. The main formed crystal phase during crystallization was solid solution of fl-quartz lithium alumino silicate, the prelemenary stage of the stable P-spodumene solid solution. Based on the JMA model, the overall activation energy of crystal growth is 29.503 kcal/mol (123.912 kJ/mol). The Avrami parameter value is 1.45, which indicates that the diffusion determines the crystallization process on a fixed number of nuclei. Whereas based on the proposed kinetic model, the overall activation energy of primary and secondary crystal growth are 24.460 kcal/mol (102.732 kJ/mol) and 24.269 kcal/mol (101.930 kJ/mol), respectively.